Performance Improvement with Web Based Database on Library Information System of Smk Yadika 5 - Pualam Dipa Nusantara (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The difficulty in managing the data of books collection in the library is a problem that is often faced by the librarian that effect the quality of service. Arrangement and recording a collection of books in the file system of separate applications Word and Excel, as well as transaction handling borrowing and returning books, therehas been no integrated records. Library system can manage the book collection. This system can reduce the problems often experienced by library staff when serving students in borrowing books. There so frequent difficulty in managing the books that still in borrowed state. This system will also record a collection of late fees or lost library conducted by students (borrowers). The conclusion of this study is library performance can be better with the library system using web database.